Functional connectivity changes in the delta frequency band following trauma treatment in complex trauma and dissociative disorder patients - Schlumpf, Yolanda R.; Nijenhuis, Ellert R. S.; Klein, Carina; Jäncke, Lutz; Bachmann, Silke (Frontiers in Psychiatry, 2022)
Objective: Phase-oriented trauma treatment is efficacious in the treatment of complex trauma and dissociative disorder patients. However, the neural correlates of this therapeutic effect are not yet well understood. In the current study we investigated whether patients show a strengthening in functional network connectivity in the delta frequency band (1 – 3.5 Hz) over the course of phase-oriented inpatient trauma treatment while they performed an emotion regulation task. Further, we examined whether neural changes were associated with symptom reduction and improvement in emotion regulation skills. Methods: Before and after eight weeks of treatment, electroencephalography (EEG) was acquired in patients (n = 28) with a complex posttraumatic stress disorder (cPTSD) or complex dissociative disorder (CDD). They also completed clinical and emotion regulation questionnaires. To delimit data variability, patients participated as one dissociative part that is referred to as Apparently Normal Part (ANP). Patients’ data were compared to a matched healthy control croup (n = 38), also measured twice. Results: Prior to treatment, functional connectivity was significantly lower in patients compared to controls during cognitive reappraisal of unpleasant pictures and passive viewing of unpleasant and neutral pictures. These hypoconnected networks largely overlapped with networks typically activated during the recall of (emotional) autobiographical memories. Functional connectivity strength within these networks significantly increased following treatment and was comparable to controls. Patients showed symptom reduction across various clinical domains and improvement in the use of cognitive reappraisal as emotion regulation strategy. Treatment-related network normalizations were not related to changes in questionnaire data. Conclusion: Phase-oriented treatment may strengthen connections between regions that are activated during autobiographical recall. These findings encourage further investigation of this circuitry as a therapeutic target in cPTSD and CDD patients. ClinicalTrials.gov/NCT02459340; https://www.kofam.ch/de/studienportal/suche/149284/studie/26681